Photolyases and Cryptochromes in UV-resistant Bacteria from High-altitude Andean Lakes - Portero, Luciano Raúl (2018)
“High-altitude Andean Lakes” (HAAL) are pristine environments harboring poly-extremophilic microbes that show combined adaptations to physical and chemical stress such as large daily ambient thermal amplitude, extreme solar radiation levels, intense dryness, alkalinity, high concentrations of arsenic (up to 200 ppm) and dissolved salts. In this work, we compared the UV resistance profiles, pigment content and photoreactivation abilities of three UV-resistant bacteria isolated from distinct niches from HAALs, that is Acinetobacter sp. Ver3 (water, Lake Verde; 4400 m), Exiguobacterium sp. S17 (stromatolite, Lake Socompa, 3570 m) and Nesterenkonia sp. Act20 (soil, Lake Socompa, 3570 m). UV resistance ability of HAAL's strains indicate a clear adaptation to high radiation exposure encountered in their original habitat, which can be explained by genetic and physiological mechanisms named as the UV-resistome. Thus, the UV-resistome depends on the expression of a diverse set of genes devoted to evading or repairing the damage it provoked direct or indirectly. As pigment extraction and photoreactive assays indicate the presence of photoactive molecules, we characterized more in detail proteins with homology to photolyases/cryptochromes members (CPF). Phylogenetic analyses, sequence comparison and 3D modeling with bona fide CPF members were used to prove the presence of functional domains and key residues in the novel proteins.